Erosive and cariogenicity potential of pediatric drugs: study of physicochemical parameters - Xavier, Alidianne Fábia C (BioMed Central, 2013)
BACKGROUND: Pediatric medications may possess a high erosive potential to dental tissues due to the existence of acid components in their formulations. The purpose was to determine the erosive and cariogenic potential of pediatric oral liquid medications through the analysis of their physicochemical properties in vitro. METHODS: A total of 59 substances were selected from the drug reference list of the National Health Surveillance Agency (ANVISA), which belong to 11 therapeutic classes, as follows: analgesics, non-steroidal anti-inflammatory, corticosteroids, antihistamines, antitussives, bronchodilators, antibacterials, antiparasitics, antiemetics, anticonvulsants and antipsychotics. Measurement of pH was performed by potentiometry, using a digital pH meter. For the Total Titratable Acidity (TTA) chemical assay, a 0.1 N NaOH standard solution was used, which was titrated until drug pH was neutralized. The Total Soluble Solids Contents (TSSC) quantification was carried out by refractometry using Brix scale and the analysis of Total Sugar Content was performed according to Fehling’s method. In addition, it was analyzed the information contained in the drug inserts with regard to the presence of sucrose and type of acid and sweetener added to the formulations. RESULTS: All drug classes showed acidic pH, and the lowest mean was found for antipsychotics (2.61 ± 0.08). There was a large variation in the TTA (0.1% - 1.18%) and SST (10.44% - 57.08%) values. High total sugar contents were identified in the antitussives (53.25%) and anticonvulsants (51.75%). As described in the drug inserts, sucrose was added in 47.5% of the formulations, as well as citric acid (39.0%), sodium saccharin (36.4%) and sorbitol (34.8%). CONCLUSION: The drugs analyzed herein showed physicochemical characteristics indicative of a cariogenic and erosive potential on dental tissues. Competent bodies’ strategies should be implemented in order to broaden the knowledge of health professionals, drug manufacturers and general consuming public about the risks from the consumption of medicines potentially harmful to dental tissues.